Growth of farm animals - Lawrence, T. L. J. [ (Tony Leonard John)]; Fowler, V. R.; Novakofski, J. E. (CABI, 2012)
An understanding of the processes that change the shape and composition of farm animals is fundamental to all aspects of production. Updated to include chapters on avian growth and global warming, this textbook provides key information on how animals grow and change in shape and composition, and the factors that affect these processes